Renal cell carcinoma or angiomyolipoma – diagnostic and therapeutic dilemmas in a 17-year-old female patient with tuberous sclerosis complex - Skrzypczyk, Piotr; Ludwiniak, Kamil; Wabik, Anna Maria; Jóźwiak, Sergiusz; Brzewski, Michał; Małdyk, Jadwiga; Pańczyk-Tomaszewska, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2023)
We present a case of a 17-year-old girl with tuberous sclerosis complex (TSC) with suspicion of renal cell carcinoma in the left kidney. Pathomorphological examination revealed domination of fusiform cells, and foci of adipocytes with a tendency towards perivascular proliferation. Immunohistochemistry revealed a positive reaction for markers of angiomyolipoma (AML): SMA (smooth muscle actin), HMB-45 (Human Melanoma Black-45), and MelanA (melanocyte antigen), and negative reaction for markers of renal cell carcinoma. In addition, positive reaction for TFE3 (transcription factor binding to immunoglobulin heavy-chain enhancer 3) was found in nuclei. The tumour was classified as a lipid-poor AML, and treatment with rapamycin was started in the patient. To the best of our knowledge, this is the first renal AML in a TSC patient in whom nuclear expression of TFE3 was found. Differential diagnosis of lipid-poor renal lesions in TSC patients is a demanding challenge requiring a dedicated, experienced multidisciplinary team.